Transarterial Endoleak Closure After Endovascular Thoracoabdominal Aneurysm Repair: When the "Sandwich" Goes Wrong. (February 2016) - Panoulas, Vasileios F.; Montorfano, Matteo; Latib, Azeem; Giustino, Gennaro; Spagnolo, Pietro; Taramasso, Maurizio; Chieffo, Alaide; Civilini, Efrem; Chiesa, Roberto; Colombo, Antonio
Purpose: To describe the use of vascular plugs to close a complex type Ib endoleak following the sandwich procedure used in conjunction with endovascular thoracoabdominal aortic aneurysm (TAAA) repair.Case Report: A 59-year-old man with a 6.5-mm TAAA was treated with initial deployment proximally of 2 Zenith TX2 stent-grafts. In preparation for the sandwich technique to preserve flow to the celiac trunk, a 10×100-mm Viabahn covered stent was delivered from a brachial access into the celiac trunk unprotected by the sheath of the introducer. The trigger wire system became snagged on the struts of the distal aortic stent-graft; when the wire was pulled, the proximal end of the Viabahn migrated outside the aortic stent-graft, which migrated upward. The main body extension intended for the aortic component of the sandwich technique was deployed close to the distal end of the aneurysm sac, but a large type Ib endoleak formed in the gutter between the Viabahn, aortic extension, and sac wall. The leak perfused the celiac trunk, and the procedure was terminated. Increasing sac size on 3-month imaging prompted closure of the leak with 2 type II Amplatzer vascular plugs aiming to occlude the endoleak outflow into the Viabahn and the endoleak outflow at the site of the gutter. Imaging follow-up at 6 months demonstrated successful exclusion of the TAAA with no residual endoleak and excellent perfusion of the celiac trunk.Conclusion: Transarterial treatment of complex endoleaks is feasible when preceded by meticulous imaging and detailed preprocedural planning.